Mobile Colloidal Organic Carbon: An Underestimated Carbon Pool in Global Carbon Cycles? - Yan, Jing; Manelski, Ronald; Vasilas, Bruce; Jin, Yan (Frontiers in Environmental Science, 2018)
Mobile colloids, 1-1000 nm particles, are ubiquitous in every ecosystem. They have small size, large specific surface area and high mobility in the subsurface, and thus can regulate the fate and transport of sorbing constituents such as nutrients, contaminants and organic carbon (OC). The movement of colloids and colloidal OC (COC) through soils is an important process in mass and energy transport (including carbon) both within and between ecosystems, e.g. from terrestrial to aquatic ecosystems, and likely contribute to the ecosystem- or global-scale carbon balance given their ubiquitous distribution and unique environmental functions. However, despite their importance for terrestrial and aquatic carbon transport and balance, colloids and COC have not been adequately accounted for because of the current operational definition uses 0.45 µm as the cutoff size for colloids. In this study, we quantified and characterized loadings of colloids and COC in aqueous samples collected from agricultural, forestry, freshwater wetland and estuary ecosystems. Results reveal that, in all samples regardless of the different sampling sources, the total colloidal loads were underestimated by ≥ 50% and considered as “dissolved” solutes when the operational definition (e.g., using a cutoff size of 0.45 m) was used. Together with a large number of data from the literature, our results further demonstrate that colloids are quantitatively substantial, carbon-dense and that as much as 8-19% of operationally defined DOC is in fact COC. Conservatively, this suggests that the COC pool potentially accounts for 13.6 TgC year-1 as a riverine flux and 530 ± 25 TgC of global DOC pool in the ocean in global carbon cycles. In addition, freshwater wetland was found to be a hotspot, which released more colloids and COC compared to the other sampled ecosystems. These findings clearly demonstrate the limitations of using the current operational definition for colloids and DOM and highlight the need for improving quantification and characterization of size-dependent colloidal and OC loads. Such effort will allow direct fundamental research into questions towards microbial access to ‘protected’ carbon by minerals and more accurate assessment of global carbon cycles.